Trends and socioeconomic disparities in financial risk protection in China 2010–16: a repeated cross-sectional analysis. Issue 1 (October 2019) - Zhao, Yang; Oldenburg, Brian; Mahal, Ajay; Tang, Shenglan; Liu, Xiaoyun
Abstract: Background: In 2009, China launched a new health system reform with the goal of achieving universal health coverage by 2020. This study aimed to assess the trends and socioeconomic disparities in financial risk protection in China, and to explore the influence of chronic diseases on catastrophic health expenditure and impoverishment due to health payments. Methods: We used data from the China Family Panel Studies 2010–16, with a sample size of 14 960 households. We defined catastrophic health expenditure as the point at which annual household health payments exceeded 40% of annual capacity to pay. Impoverishment was defined as earning below the poverty line of $1·90 per day. We used multivariate logistic regression models to identify the effects of the costs incurred by a family member with chronic disease on catastrophic health expenditure and impoverishment. Ethics permission and approval were obtained from the Peking University Biomedical Ethics Review Committee (IRB00001052-14010). Findings: Between Aug 13, 2010 and June 28, 2016, the incidence of catastrophic health expenditure in China decreased from 19·37% (95% CI 17·91–20·93) to 15·11% (14·09–16·12), and from 7·34% (6·54–8·14) to 5·14% (4·53–5·74) for health impoverishment; however, the decrease in impoverishment was less in rural areas (from 8·46% to 7·81%) than in urban areas (from 6·16% to 3·03%) in 2010–16 (p<0·0001). The gap between the prevalence of impoverishment across the income quartiles has grown. Multivariable analysis showed that households with two or more people with chronic diseases were significantly more likely to incur catastrophic health expenditure (odds ratio 2·46 [95% CI 1·93–3·13]) and impoverishment (2·66 [1·87–3·78]) compared with households with no people with chronic diseases, after adjusting for sociodemographic covariates. Interpretation: Important advances have been made in improving financial protection for Chinese citizens. Nevertheless, increased attention to poor and rural households with people with chronic diseases is needed. Policymakers in China should focus on optimising integrated rural–urban health insurance by expanding the existing benefit packages. Moreover, increased efforts to alleviate poverty should be continued through further development of China's medical assistance system for poor people. Funding: None.